A novel strategy for selective gene delivery by using the inhibitory effect of blue light on jetPRIME‐mediated transfection. Issue 7 (30th December 2015) - Dateki, Minori; Imamura, Osamu; Arai, Masaaki; Shimizu, Hidehisa; Takishima, Kunio
ABSTRACT: Photodynamic control of gene delivery is a new technology with growing applications in gene therapy and basic cell research. Main approaches of light‐selective gene delivery rely on the light‐dependent enhancement of transfection efficiency. Studies focused on light‐stimulated inhibitory regulation of transfection have rarely been reported. Here, we tried to establish a novel procedure of light‐dependent inhibition of transfection. Our experiments, conducted with several types of commercial transfection reagents, revealed that jetPRIME‐mediated transfection was strongly inhibited by blue light. Although the uptake of reagent–DNA complex was drastically reduced, preliminary exposure of cells or reagent–DNA complex to blue light had no inhibitory effect on the transfection efficiency. The inhibitory effect was wavelength‐dependent and mediated by reactive oxygen species. Partial exposure of a culture vessel to blue light resulted in selective gene delivery into cells grown on the unexposed area of the vessel. By using this approach, different types of plasmid DNA were delivered into different areas in the culture vessel. This novel approach to the inhibitory control of transfection provides practical options for research and therapeutics. Biotechnol. Bioeng. 2016;113: 1560–1567. © 2015 Wiley Periodicals, Inc. Abstract : Photodynamic control of gene delivery is a new technology with growing applications in gene therapy and basic cell research. Screening for photoreactive transfection reagents in commercial transfection products revealed that jetPRIME‐mediated transfection was strongly inhibited by blue‐light irradiation. Partial exposure of the culture dish to blue light caused selective gene delivery in the unexposed area (A) and enabled delivery of different plasmid DNAs to different areas (B). Present study provides novel practical option for selective gene delivery.